Alcrfeni multi-principal element alloy material with high strength and high plasticity and thermal stability and preparation method thereof
Patent Information
- Application Number
- CN202511281260.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2045-09-09
AI Technical Summary
[0005]为解决当前AlCrFeNi多主元合金材料存在强塑性匹配不佳与微观结构不可控的问题,本发明提供了一种兼具高强度高塑性和热稳定性的AlCrFeNi多主元合金材料及其制备方法
[0026]本发明通过枝晶双相组织设计,实现了AlCrFeNi多主元合金强度与塑性的协同优化。铸态合金室温拉伸延伸率达27%,屈服强度364 MPa,抗拉强度905 MPa,显著优于传统AlCrFeNi合金,彻底解决了该体系合金室温脆性难题,使其具备拉伸成型能力,大幅拓宽了加工工艺窗口。退火后合金仍保持12%延伸率,同时屈服强度提升至799 MPa,抗拉强度达1213 MPa,突破了“退火软化”的技术瓶颈,为复杂构件的成型与后续热处理提供了性能保障。
Smart Images

Figure CN121137435B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of multi-principal element alloy materials technology, and particularly relates to an AlCrFeNi multi-principal element alloy material with high strength, high plasticity and thermal stability and its preparation method. Background Technology
[0002] AlCrFeNi multi-principal-element alloys possess excellent properties such as high strength, high hardness, good wear resistance, high-temperature creep resistance, and corrosion resistance, making them promising for applications in aerospace, automotive manufacturing, and energy. However, current technology still faces two major challenges: an imbalance between strength and plasticity, and difficulties in the directional control of microstructure, which severely restrict their engineering applications.
[0003] AlCrFeNi alloys prepared by existing technologies generally exhibit the typical characteristics of "high strength but low plasticity," with their compressive fracture strain typically less than 25%. Due to severe brittleness, most AlCrFeNi alloys can only complete compression tests, while they are prone to brittle fracture in tensile tests. This makes them unable to meet the toughness requirements (such as impact resistance and fatigue resistance) of practical engineering, significantly limiting their application scenarios.
[0004] The formation mechanism of nanoscale dendrites in AlCrFeNi multi-principal element alloys is unpredictable because dendrite growth is jointly controlled by thermodynamics (compositional supercooling) and kinetics (solute diffusion). However, the complex interactions among the multiple components in AlCrFeNi alloys lead to a lack of theoretical predictive models for dendrite morphology. Experimentally, dendrite size fluctuates significantly, making precise control through process parameters difficult. Alloy properties depend on the synergistic effects of multi-scale structures such as grain size, phase composition, and precipitated phases, but current technologies cannot simultaneously control these characteristics. While additive manufacturing can refine grains to the nanoscale, it easily induces elemental segregation; arc melting can achieve a uniform phase composition but struggles to control dendrite size. Therefore, current technologies have not yet overcome the challenge of precisely controlling multi-scale microstructures, preventing the targeted design and optimization of microstructures. Summary of the Invention
[0005] To address the problems of poor strength-plasticity matching and uncontrollable microstructure in current AlCrFeNi multi-principal alloy materials, this invention provides an AlCrFeNi multi-principal alloy material with high strength, high plasticity, and thermal stability, as well as its preparation method.
[0006] The technical solution of the present invention:
[0007] An AlCrFeNi multi-principal-element alloy material with high strength, high plasticity and thermal stability contains the following alloy composition: Al: 6~7 wt%, Cr: 23~27 wt%, Fe: 28~33 wt% and Ni: 34~39 wt%.
[0008] Furthermore, it contains the following alloy composition: Al: 6.83 wt%, Cr: 25.56 wt%, Fe: 31.07 wt%, and Ni: 36.54 wt%.
[0009] A method for preparing an AlCrFeNi multi-principal-element alloy material with high strength, high plasticity, and thermal stability, comprising the following steps:
[0010] Step 1: Predicting and designing alloy microstructure through phase-field simulation:
[0011] Using a continuous phase-field model, a pseudo-binary method was employed to simplify the AlCrFeNi alloy. Fe and Cr elements were defined as component A, and Ni and Al elements as component B. The free energy formula obtained through thermodynamic calculations is shown in Equation 1.
[0012] (1)
[0013] In the formula : Non-conservative phase field parameter, with a value of 1 in solids and zero in liquids; m: interfacial motion driving force proportional to supercooling;
[0014] Substituting the fitted free energy formula into the phase field model, and combining the temperature and composition fields, the precipitation behavior of the alloy under different cooling rates is simulated. By fitting and predicting the solid solution precipitation phase transformation process of the alloy at different temperatures, alloy compositions capable of forming dendritic dual-phase structures are screened. The alloy compositions correspond to a molar ratio of A to B components of 1:1.2, and the specific alloy compositions are: Al: 6~7 wt%, Cr: 23~27 wt%, Fe: 28~33 wt%, and Ni: 34~39 wt%.
[0015] Step 2: Select pure metals with a purity greater than 99.9% as raw materials, weigh the raw materials according to the proportion, clean and dry them, put them into a crucible and load them into a vacuum induction furnace.
[0016] Step 3: After evacuating the vacuum induction furnace, fill it with high-purity argon gas to a certain pressure.
[0017] Step 4: Melt the various metal raw materials by induction heating, promote uniform mixing by electromagnetic stirring, and cast to obtain the as-cast AlCrFeNi multi-principal element alloy.
[0018] Step 5: Heat treat the as-cast AlCrFeNi multi-principal-element alloy to obtain the annealed AlCrFeNi multi-principal-element alloy.
[0019] Furthermore, the alloy composition described in step one is: Al: 6.83 wt%, Cr: 25.56 wt%, Fe: 31.07 wt%, and Ni: 36.54 wt%.
[0020] Furthermore, the vacuum level achieved in step three is 10. -2 ~10 -3 Pa, wherein the pressure of the high-purity argon gas is 0.05~0.1 MPa.
[0021] Furthermore, the frequency of induction heating in step four is 2~10 kHz, and the induction heating temperature is 1500℃.
[0022] Furthermore, in step four, the uniformly mixed liquid alloy is first kept at a constant temperature for 5-15 minutes to allow impurities to precipitate before casting.
[0023] Furthermore, in step five, the heat treatment involves heating the obtained as-cast AlCrFeNi multi-principal alloy to 900 °C at a first heating rate, then continuing to heat it to 1200 °C at a second heating rate, holding it at that temperature for 6 hours, and then furnace cooling it to room temperature.
[0024] Furthermore, the first heating rate is 10 ℃ / min, and the second heating rate is 5 ℃ / min.
[0025] The beneficial effects of this invention are:
[0026] This invention achieves synergistic optimization of strength and plasticity in AlCrFeNi multi-principal element alloys through dendritic dual-phase microstructure design. The as-cast alloy exhibits a room-temperature tensile elongation of 27%, a yield strength of 364 MPa, and a tensile strength of 905 MPa, significantly superior to traditional AlCrFeNi alloys. This completely solves the room-temperature brittleness problem of this alloy system, enabling it to be stretched and formed, and greatly expanding the processing window. After annealing, the alloy retains 12% elongation, while the yield strength increases to 799 MPa and the tensile strength reaches 1213 MPa, breaking through the technical bottleneck of "annealing softening" and providing performance assurance for the forming and subsequent heat treatment of complex components.
[0027] This invention predicts the microstructure of alloys through phase-field simulation, and achieves the design goal of a dendritic two-phase structure in AlCrFeNi multi-principal element alloys through composition optimization and annealing at 1200 °C. This structure enhances strength by hindering dislocation movement through dendrites and retains plasticity through a phase interface sliding mechanism. After annealing, the nano-precipitates are further refined and uniformly distributed, avoiding embrittlement caused by grain boundary coarsening and endowing the alloy with excellent thermal stability. Experiments show that the strength increases rather than decreases after annealing, with tensile strengths reaching 252 MPa in the as-cast state and 243 MPa in the annealed state at 800 °C, demonstrating the supporting role of microstructure stability in high-temperature performance.
[0028] The AlCrFeNi multi-principal element alloy prepared by this invention exhibits excellent performance at room temperature, high temperature, and after heat treatment. The strength enhancement characteristic after annealing solves the problem of performance degradation during service. Furthermore, the alloy composition does not contain precious metals such as Co, Cu, and Ti. Through optimized proportions of Al, Cr, Fe, and Ni, raw material costs are reduced by more than 30% while maintaining performance. Combined with precise microstructure prediction using phase-field simulation technology, this alloy achieves a breakthrough in "low cost, high performance, and easy processing," providing a cost-effective material solution for aerospace, energy equipment, and other fields. Attached Figure Description
[0029] Figure 1 AlCr2Fe2Ni in as-cast state 2.5 Photos of actual alloy ingots;
[0030] Figure 2 AlCr2Fe2Ni in as-cast state 2.5 Microstructure of alloy material at 25℃;
[0031] Figure 3 AlCr2Fe2Ni in as-cast and 6h annealed states 2.5 Comparison of XRD (X-ray diffraction) results for alloy materials;
[0032] Figure 4 AlCr2Fe2Ni in as-cast and 6h annealed states 2.5 SEM images of the alloy microstructure, (a) in the as-cast state, (b) in the 6h annealed state;
[0033] Figure 5 AlCr2Fe2Ni in as-cast and 6h annealed states 2.5 Stress-strain curves of alloy microstructures under room temperature tensile engineering.
[0034] Figure 6 AlCr2Fe2Ni in as-cast and 6h annealed states 2.5 Stress-strain curves of high-temperature tensile engineering in alloy structures, (a) is the as-cast state, (b) is the 6h annealed state. Detailed Implementation
[0035] The technical solution of the present invention will be further described below with reference to embodiments, but it is not limited thereto. Any modifications or equivalent substitutions to the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be covered within the protection scope of the present invention. In the following embodiments, the process equipment or apparatus not specifically specified are all conventional equipment or apparatus in the art. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available; unless otherwise specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0036] Example 1
[0037] This embodiment provides a method for preparing AlCrFeNi multi-principal-element alloy materials that combine high strength, high plasticity, and thermal stability. The specific preparation steps are as follows:
[0038] Step 1: Phase-field simulation for prediction and design of alloy microstructure:
[0039] Using a continuous phase-field model, a pseudo-binary method was employed to simplify the AlCrFeNi alloy, defining Fe and Cr as component A and Ni and Al as component B. The alloy composition proposed in this embodiment corresponds to a molar ratio of approximately 1:1.2 for components A and B. The free energy formula obtained through thermodynamic calculations is shown in Equation 1.
[0040] (1)
[0041] In the formula : Non-conservative phase field parameter, with a value of 1 in solids and zero in liquids; m: interfacial motion driving force proportional to supercooling;
[0042] Thus, the solid solution precipitation phase transformation process of the alloy after cooling at 1300 °C was simulated.
[0043] After screening and optimization, the alloy composition was obtained as follows: Al: 6.83 wt%, Cr: 25.56 wt%, Fe: 31.07 wt%, and Ni: 36.54 wt%.
[0044] Step 2: Select pure metal particles Al, Cr, Fe and Ni with a purity greater than 99.9% as raw materials, weigh the raw materials according to the proportion, clean and dry them, put them into a crucible and load them into a vacuum induction furnace.
[0045] Step 3: At the start of melting, turn on the mechanical pump. After 3 minutes, open the Roots valve to evacuate to 10°C. -3 Pa, fill with high-purity argon gas to 0.08 MPa;
[0046] Step 4: Induction heat to 1500 ℃ at 10 kHz, promote uniform mixing by electromagnetic stirring, hold at this temperature for 15 min, and then pour to obtain the as-cast AlCrFeNi multi-principal element alloy, with the appearance as shown in the figure. Figure 1 As shown in Table 1, the elemental content of the as-cast alloy was determined using a NexION 350X inductively coupled plasma optical emission spectrometer. The alloy was named AlCr2Fe2Ni. 2.5 alloy.
[0047] Table 1
[0048]
[0049] Step 5: Apply a conventional heat treatment anti-oxidation coating to the surface of the alloy ingot evenly, let it air dry naturally, and then place it in a muffle furnace. Before heat treatment, the muffle furnace is calibrated to ensure that the temperature error is within ±5 °C.
[0050] As-cast AlCr2Fe2Ni 2.5 The alloy was placed in a muffle furnace and heated to 900 °C at a heating rate of 10 °C / min, then further heated to 1200 °C at a heating rate of 5 °C / min, and held at 1200 °C for 6 h. After furnace cooling to room temperature, annealed AlCr2Fe2Ni with an annealing time of 6 h was obtained. 2.5 alloy.
[0051] Figure 2 AlCr2Fe2Ni in as-cast state 2.5 Microstructure of the alloy at 25°C, by Figure 2 It can be seen that the design goal of the alloy is to obtain a dendritic dual-phase structure.
[0052] The as-cast AlCr2Fe2Ni prepared in Example 1 2.5 Alloy and 6h annealed AlCr2Fe2Ni 2.5 The alloy was characterized by its microstructure and its properties were tested.
[0053] I. Phase analysis was performed using an Empyrean intelligent X-ray diffractometer.
[0054] The operating conditions are Cu target Kα radiation, Ni filter, and tube power of 2.2 kW. The diffraction angle range is 20-100°, and the velocity is 5° / min.
[0055] As-cast AlCr2Fe2Ni 2.5 The phase composition of the alloy is as follows Figure 3 As shown, the alloy consists of phases A1, A2, and B2. A1 is a disordered [Fe, Cr] phase, A2 is an ordered NiAl phase, and the B2 phase is mainly composed of Fe and Ni elements. After annealing, the alloy phase composition remains unchanged. With the extension of annealing time, the peak area corresponding to 2θ = 44.62 ° increases, indicating an increase in the content of the BCC phase.
[0056] II. The microstructure of the material was observed using a Hitachi scanning electron microscope SU 5000.
[0057] AlCr2Fe2Ni 2.5 SEM images of the microstructure of the as-cast alloy, as shown Figure 4As shown in (a), the structure exhibits banded and petal-like dendrite morphologies within a large-area network-like dual-phase microstructure. The main dendritic elements are Fe and Cr, corresponding to the light-colored precipitates. The main interdendritic elements are Ni and Al, corresponding to the dark-colored matrix. After annealing for 6 hours, AlCr2Fe2Ni... 2.5 The alloy maintained its dendritic morphology unchanged. Figure 4 (b) Secondary electron scanning images show that AlCr2Fe2Ni 2.5 After annealing, the network-like two-phase dendrites gradually disappeared, evolving into banded structures. This is because annealing promotes element diffusion in the alloy, reducing the difference in element distribution compared to the as-cast state. Al and Cr elements are mainly distributed between dendrites, while the distribution of Fe and Ni elements shows less difference. Combined with XRD results, Fe and Al elements, as well as Ni and Cr elements, undergo atomic substitution, forming the [Fe, Ni] A2 phase and the AlFe B2 phase.
[0058] III. The density of the alloy was determined using the Archimedes displacement method, and the density of the as-cast AlCr2Fe2Ni prepared in Example 1 was measured. 2.5 The alloy has a density of 7.30 g / cm³. 3 .
[0059] IV. Detection of the DSC (Differential Scanning Calorimetry) curve of the alloy, specifically the as-cast AlCr2Fe2Ni alloy prepared in Example 1. 2.5 The alloy has a melting point of 1351 °C.
[0060] 5. Hardness testing was performed using an HVS-1000 digital display microhardness tester.
[0061] Before testing, the samples were polished after being successively ground with 240-grit and 400-grit sandpaper. The test conditions were set as follows: 0.5 kgf test load, 10 s hold time, and 5 different test points were selected for each sample for measurement.
[0062] As-cast AlCr2Fe2Ni 2.5 The alloy has a microhardness of 336 kgf / mm. 2 The hardness decreased by 20 kgf / mm after annealing. 2 It remains at a high level.
[0063] VI. Room temperature tensile properties were tested using an Instron 5500R electronic universal testing machine at a loading speed of 1 mm / min. Plate-shaped tensile specimens were prepared using wire electrical discharge machining (EDM). Specific geometric dimensions are detailed in [reference needed]. Figure 1 As shown, the thickness is 1 mm. Two samples were cut from each component, and the upper and lower end faces were ground flat.
[0064] As-cast AlCr2Fe2Ni prepared in Example 1 2.5 Alloy and AlCr2Fe2Ni annealed for 6 hours 2.5 The room temperature tensile properties of the alloy are shown in Table 2 and Figure 4 As shown.
[0065] Table 2
[0066]
[0067] As shown in Table 2, the as-cast AlCr2Fe2Ni 2.5 The alloy exhibits an elongation of 27%, a yield strength of 364 MPa, and a tensile fracture strength of 905 MPa. Maintaining strength while demonstrating higher elongation compared to previously reported alloys indicates excellent plasticity, addressing the brittleness issue of this alloy system at room temperature and facilitating processing and forming. After annealing, the yield strength significantly increases to 799 MPa, and the tensile strength increases to 1213 MPa, which is attributed to reduced lattice distortion after annealing. This strength improvement indicates that AlCr2Fe2Ni... 2.5 The alloy exhibits excellent thermal stability and possesses certain heat treatment capabilities, thus solving the problem of strength reduction after annealing common in many alloys and improving its practical applicability.
[0068] Meanwhile, its engineering stress-strain curve Figure 4 It can be seen that the as-cast and annealed states of AlCr2Fe2Ni 2.5 All alloys exhibit necking-free elongation during room temperature stretching, demonstrating excellent room temperature tensile properties.
[0069] VII. High-temperature tensile properties were tested using an AG-X Plus250Kn / 50Kn electronic universal testing machine. Two specimens were cut from each component and polished to 1000-grit sandpaper. The specimen thickness was 1 mm. The heating rate was 15 °C / min, the holding time was 5 min, and the loading rate was 1 mm / min.
[0070] As-cast AlCr2Fe2Ni prepared in Example 1 2.5 Alloy and AlCr2Fe2Ni annealed for 6 hours 2.5 The tensile test results of the alloy at 800 ℃, 900 ℃, and 1000 ℃ are shown in Table 3 and... Figure 6 As shown.
[0071] Table 3
[0072]
[0073] The tensile test results at 800 ℃, 900 ℃, and 1000 ℃ are shown in Table 3, and the engineering stress-strain curves are shown in Table 3. Figure 6 As shown. As-cast AlCr2Fe2Ni at 800 ℃ 2.5 The alloy has a tensile strength of 252 MPa, which increases to 243 MPa after annealing, exhibiting high high-temperature strength. The tensile properties of the alloy at 900 ℃ and 1000 ℃ differ significantly from those at 800 ℃. This difference is... Figure 6 The difference is more pronounced in the middle. After 900 ℃, the strength decreases to 142 MPa, but the elongation increases significantly to 41%.
[0074] The annealed alloy exhibits similar tensile properties at high temperatures to the as-cast alloy, with a tensile strength of 243 MPa at 800 °C. The microstructure coarsening caused by annealing did not significantly affect the strength. The elongation was 7%, essentially consistent with the as-cast alloy. With increasing test temperature, the yield strength decreased to 133 MPa, and the tensile strength decreased to 146 MPa. Furthermore, due to necking and dynamic recrystallization, the strength initially reached its maximum during tensile testing, subsequently decreasing with increasing strain.
Claims
1. An AlCrFeNi multi-principal element alloy material possessing high strength, high plasticity, and thermal stability, characterized in that, It contains the following alloy composition: Al: 6~7 wt%, Cr: 23~27 wt%, Fe: 28~33 wt%, and Ni: 34~39 wt%; and the AlCrFeNi multi-principal element alloy material has a dendritic dual-phase structure.
2. The AlCrFeNi multi-principal element alloy material with high strength, high plasticity, and thermal stability according to claim 1, characterized in that, It contains the following alloy composition: Al: 6.83 wt%, Cr: 25.56 wt%, Fe: 31.07 wt%, and Ni: 36.54 wt%.
3. A method for preparing an AlCrFeNi multi-principal-element alloy material possessing high strength, high plasticity, and thermal stability, characterized in that, The steps are as follows: Step 1: Predicting and designing alloy microstructure through phase-field simulation: Using a continuous phase-field model, a pseudo-binary method was employed to simplify the AlCrFeNi alloy. Fe and Cr elements were defined as component A, and Ni and Al elements as component B. The free energy formula obtained through thermodynamic calculations is shown in Equation 1. (1) In the formula : Non-conserved phase field parameter, takes a value of 1 in solids and a value of zero in liquids; m: the interfacial motion driving force proportional to the degree of supercooling; Substituting the fitted free energy formula into the phase field model, and combining the temperature and composition fields, the precipitation behavior of the alloy under different cooling rates is simulated. By fitting and predicting the solid solution precipitation phase transformation process of the alloy at different temperatures, alloy compositions capable of forming dendritic dual-phase structures are screened. The alloy compositions correspond to a molar ratio of A to B components of 1:1.2, and the specific alloy compositions are: Al: 6~7 wt%, Cr: 23~27 wt%, Fe: 28~33 wt%, and Ni: 34~39 wt%. Step 2: Select pure metals with a purity greater than 99.9% as raw materials, weigh the raw materials according to the proportion, clean and dry them, put them into a crucible and load them into a vacuum induction furnace. Step 3: After evacuating the vacuum induction furnace, fill it with high-purity argon gas to a certain pressure; Step 4: Melt the various metal raw materials by induction heating, promote uniform mixing by electromagnetic stirring, and cast to obtain the as-cast AlCrFeNi multi-principal element alloy. Step 5: Heat-treat the as-cast AlCrFeNi multi-principal alloy by heating it to 900 ℃ at a first heating rate of 10 ℃ / min, and then continuing to heat it to 1200 ℃ at a second heating rate of 5 ℃ / min. After holding at this temperature for 6 hours, furnace cool it to room temperature to obtain the annealed AlCrFeNi multi-principal alloy.
4. The method for preparing the AlCrFeNi multi-principal-element alloy material with high strength, high plasticity, and thermal stability according to claim 3, characterized in that, The alloy composition described in step one is: Al: 6.83 wt%, Cr: 25.56 wt%, Fe: 31.07 wt%, and Ni: 36.54 wt%.
5. The method for preparing the AlCrFeNi multi-principal-element alloy material with high strength, high plasticity, and thermal stability according to claim 4, characterized in that, The vacuum level described in step three is 10. -2 ~10 -3 Pa, wherein the pressure of the high-purity argon gas is 0.05~0.1 MPa.
6. The method for preparing the AlCrFeNi multi-principal-element alloy material with high strength, high plasticity, and thermal stability according to claim 5, characterized in that, The frequency of induction heating in step four is 2~10 kHz, and the induction heating temperature is 1500℃.
7. The method for preparing the AlCrFeNi multi-principal-element alloy material with high strength, high plasticity, and thermal stability according to claim 6, characterized in that, Step 4: The uniformly mixed liquid alloy is first kept at a constant temperature for 5-15 minutes to allow impurities to settle before casting.
Citation Information
Patent Citations
Multi-scale chain type integrated design method of structural material and database system
CN114974474A
High-strength corrosion-resistant AlCrFeNi medium-entropy alloy as well as preparation method and application thereof
CN117778854A
Nickel-iron-aluminum-chromium based alloys, and products made therefrom
US20190024225A1
